Unveiling the carbon-reduction potential of data sharing: A quasi-experimental investigation of public data open platforms in Chinese cities - Chengxing Xie; Yue Wang; Weilong Wang; Liang Wu (PLoS ONE, 2025)
Existing research predominantly delves into the environmental governance performance of the digital economy, ignoring the latent values of data factors. Public Data Open Platforms (PDOPs) have released vast amounts of public data, fostering high-level applications of data across multiple industries and domains. By employing panel data from 281 cities in China spanning 2006–2021, we empirically verify the impact of PDOPs on city-level carbon reduction, supported by various robustness tests, including the PSM-DID and placebo tests. Moreover, we emphasize that promoting green technology innovation and optimizing resource allocation efficiency are pivotal pathways through which PDOPs can enhance their carbon reduction effects. Heterogeneity analysis reveals that cities with more advanced digital infrastructure and higher market integration experience a more pronounced carbon reduction impact from PDOPs. Additionally, resource-abundant cities benefit more from PDOPs’ carbon reduction effects than resource-scarce ones.